Growth of Dyera polyphylla and Shorea balangeran Seedlings on Various Growing Media for Restoration Program - Lilis Setyawati; Istomo; Leti Sundawati; Hesti Lestari Tata (Jurnal Sylva Lestari, 2023)
The success of peat swamp ecosystem restoration needs to be supported by the supply of good quality native plant species, one of which is influenced by the growing media. This study aimed to evaluate the effect of cocopeat, compost, and biochar as a mixture of peat media on the growth of Dyera polyphylla and Shorea balangeran seedlings in a greenhouse for six months. The experiment was carried out using a completely randomized design with one factor, growing media (100% peat as M1 (control); 70% peat + 30% cocopeat as M2; 70% peat + 30% compost as M3; and 70% peat + biochar 30% as M4). The survival rate of both types of seedlings in all growing media treatments was 100%. Dickson Quality Index (DQI) of D. polyphylla seedlings on M1, M2, M3, and M4 was 0.32, 0.29, 0.46, and 0.31, respectively, and for S. balangeran was 0.15, 0.10, 0.09, and 0.12, respectively. Adding cocopeat, compost, and biochar could increase the nutrient content of peat media. The growing media with the best quality for D. polyphylla was M3, while for S. balangeran was M1. Keywords: Dickson Quality Index, Dyera polyphylla, growing media, growth response, Shorea balangeran